PENINGKATAN PEMAHAMAN DAN IMPLEMENTASI LITERASI KEUANGAN PADA UMKM DESA SITUSARI KECAMATAN DARMA KABUPATEN KUNINGAN - Januar Habibi Mahsyar (Taroa: Jurnal Pengabdian Masyarakat, 2023)
Financial literacy is very important for someone to make decisions, especially in relation to daily activities, making decisions about saving or investing to achieve certain goals. MSME entrepreneurs must have financial literacy to contribute to their business. Siteari Village is one of 19 villages in Darma District, Kuningan Regency, which has MSMEs with problems of lack of understanding regarding financial literacy, so counseling and financial management assistance is needed with the aim of having a significant impact on business continuity and development. The financial literacy outreach activity for the UMKM in Siteari Village was carried out on September 24, 2022, the implementation of the activity went well, was enthusiastically attended by UMKM players in Siteari Village and had an extraordinary role for MSMEs to get to know and be able to sell MSME bookkeeping better. Based on the results of interviews with the participants in Improving Understanding and Implementation of Financial Literacy at Umkm, Siteari Village, Darma District, Kuningan Regency, the participants gave satisfaction scores with the material presented.